2001
DOI: 10.1097/00004836-200110000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sclerosing Cholangitis in Patients With Inflammatory Bowel Disease in Turkey

Abstract: Prevalence of PSC-associated IBD in the Turkish community appear to be similar to the results of western origin studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Although the incidence of this progressive cholestatic liver disease is rare (3%), it requires careful follow-up since it is a slowly progressive disease over many years and leads to hepatic failure. In a recent paper from Turkey, Parlak et al [27]identified an incidence of 2.3% in their PSC population, which was similar to our own findings. The mean age at diagnosis was 43.6 in patients with UC.…”
Section: Discussionsupporting
confidence: 90%
“…Although the incidence of this progressive cholestatic liver disease is rare (3%), it requires careful follow-up since it is a slowly progressive disease over many years and leads to hepatic failure. In a recent paper from Turkey, Parlak et al [27]identified an incidence of 2.3% in their PSC population, which was similar to our own findings. The mean age at diagnosis was 43.6 in patients with UC.…”
Section: Discussionsupporting
confidence: 90%
“…However, studies from Central Asia and the Middle East have more variable results. Generally, PSC-IBD concurrence rates in these regions are reported as similar to those in Europe, but PSC-UC concurrence rates are much lower, often under 60%[ 16 , 60 , 61 ]. Lastly, some regions, such as central and southern Europe, Alaska, and northern Canada have identified either very low or even no concurrence of PSC with IBD[ 62 - 64 ].…”
Section: Primary Sclerosing Cholangitis and Inflammatory Bowel Diseasmentioning
confidence: 99%
“…The annual incidence of CCA among adult and pediatric patients with PSC is roughly 7%-9% across populations, though estimates in North America vary greatly, with reported incidences as low as 4% and as high as 20%[ 1 , 11 , 42 , 65 - 67 ]. The highest annual incidence of CCA is in Asia, with incidences as high as three times the global average; the reason for this elevated incidence is unknown (Table 1 )[ 16 , 35 , 60 , 68 , 69 ]. Interestingly, the highest non-PSC related rates of CCA are also seen in Asia, suggesting another variable ( e.g ., parasitic infections and chronic viral hepatitis) may be playing a role in the high rate of CCA[ 70 ].…”
Section: Primary Sclerosing Cholangitis and Neoplasiamentioning
confidence: 99%
“…The liver can be affected, as manifested by primary sclerosing cholangitis or autoimmune hepatitis. Disease-specific treatment has to be applied [36].…”
Section: Extra-intestinal Manifestationmentioning
confidence: 99%